Exergy analysis of synthetic biofuel production via fast pyrolysis and hydroupgrading. (1st January 2015) - Peters, Jens F.; Petrakopoulou, Fontina; Dufour, Javier
Abstract: This paper presents the first assessment of the exergetic performance of a biorefinery process based on catalytic hydroupgrading of bio-oil from fast pyrolysis. Lignocellulosic biomass is converted into bio-oil through fast pyrolysis, which is then upgraded to synthetic fuels in a catalytic hydrotreating process. The biorefinery process is simulated numerically using commercial software and analyzed using exergetic analysis. Exergy balances are defined for each component of the plant and the exergetic efficiencies and exergy destruction rates are calculated at the component, section and plant level, identifying thermodynamic inefficiencies and revealing the potential for further improvement of the process. The overall biofuel process results in an exergetic efficiency of 60.1%, while the exergetic efficiency of the upgrading process in the biorefinery alone is 77.7%. Within the biorefinery, the steam reforming reactor is the main source of inefficiencies, followed by the two hydrotreating reactors. In spite of the high operating pressures in the hydrotreating section, the compressors have little impact on the total exergy destruction. Compared to competing lignocellulosic biofuel processes, like gasification with Fischer–Tropsch synthesis or lignocellulosic ethanol processes, the examined system achieves a significantly higher exergetic efficiency. Highlights: Exergetic analysis of a biorefinery for bio-oil hydroupgrading. Detailed simulation model using 83 model compounds. Exergy destruction quantified in each component of the plant. Exergetic efficiency and potential for improvement determined on component level. Highest exergy destruction in the pyrolysis plant and the steam reformer.